2011
DOI: 10.1111/j.2042-3292.2011.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Advances in diagnostic imaging of the larynx and pharynx

Abstract: Summary Imaging of the larynx and pharynx has traditionally been limited to upper airway endoscopy and radiography. Recently, ultrasonography, magnetic resonance imaging and computed tomography have become used more widely. These modalities have increased our diagnostic yield when investigating disorders of the upper airway. The Case Report in this issue (Koenig et al. 2012) describes the diagnosis and biopsy of a laryngeal mass using ultrasonography illustrating one novel application of laryngeal ultrasonogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Each horse underwent standing upper respiratory endoscopy to visualize the laryngeal structures and grade the presurgical laryngeal hemiplegia using the Havemeyer system (http://Portoscopes.com 12.9 mm portable video endoscope, http://Portoscope.com, Bradenton, Florida). Postsurgical endoscopic laryngeal grading used the Dixon system . Any complications were noted.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each horse underwent standing upper respiratory endoscopy to visualize the laryngeal structures and grade the presurgical laryngeal hemiplegia using the Havemeyer system (http://Portoscopes.com 12.9 mm portable video endoscope, http://Portoscope.com, Bradenton, Florida). Postsurgical endoscopic laryngeal grading used the Dixon system . Any complications were noted.…”
Section: Methodsmentioning
confidence: 99%
“…Laryngoplasty, with or without ventriculocordectomy, is a standard treatment for laryngeal hemiplegia . Endoscopy is used to evaluate and monitor equine postsurgical laryngoplasty as the gold standard, however, this modality is limited in assessment of peri‐ and non‐luminal laryngeal structures . Laryngoplasty is associated with a number of postsurgical complications, primarily: surgical wound infection, failure to maintain abduction, coughing, prosthetic infection, and aspiration pneumonia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the report by Tessier et al, the MR imaging technique was used to diagnose sinusitis, paranasal sinus cysts, ethmoid hematoma, and neoplasia [54]. Garrett et al reported MR as an advanced imaging method of larynx and pharynx, presenting MR features of laryngeal dysplasia and laryngeal cystlike malformation [43,55,56]. Potentially, the MR might be a superior imaging technique in the diagnosis of foal lung diseases, following the experiences from human medicine.…”
Section: Clinical Applicationsmentioning
confidence: 99%